The zhuyu pill relieves rat cholestasis by regulating the mRNA expression of lipid and bile metabolism associated genes - Han, Jun; Wu, Peijie; Wen, Yueqiang; Liu, Chao; Liu, Xinglong; Tao, Huan; Zhang, Fenghua; Zhang, Xiaodan; Ye, Qiaobo; Shen, Tao; Chen, Xiaofeng; Yu, Han (Frontiers in Pharmacology, 2023)
Background: The Zhuyu pill (ZYP), composed of Coptis chinensis Franch. and Tetradium ruticarpum (A. Jussieu) T. G. Hartley, is an effective traditional Chinese medicine with potential anti-cholestatic effects. However, the underlying mechanisms of ZYP remain unknown.Objective: To investigate the mechanism underlying the interventional effect of ZYP on mRNA-seq analysis in cholestasis rat models.Materials and methods: This study tested the effects of a low-dose (0.6 g/kg) and high-dose (1.2 g/kg) of ZYP on a cholestasis rat model induced by α-naphthylisothiocyanate (ANIT, 50 mg/kg). Serum biochemistry and histopathology results were used to evaluate the therapeutic effect of ZYP, and mRNA-Seq analysis was performed and verified using real-time fluorescence quantitative PCR (qRT-PCR). GO, KEGG, and GSEA analyses were integrated to identify the mechanism by which ZYP impacted cholestatic rats.Results: ZYP was shown to significantly improve abnormal changes in the biochemical blood indexes and liver histopathology of cholestasis rats and regulate pathways related to bile and lipid metabolism, including fatty acid metabolism, retinol metabolism, and steroid hormone biosynthesis, to alleviate inflammation, cholestasis, and lipid metabolism disorders. Relative expression of the essential genes Cyp2a1, Ephx2, Acox2, Cyp1a2, Cyp2c11, and Sult2a1 was verified by qRT-PCR and showed the same trend as mRNA-seq analysis.Conclusions: ZYP has a significant anti-cholestatic effect by regulating bile metabolism and lipid metabolism related pathways. These findings indicate that ZYP is a novel and promising prospect for treating cholestasis.